Validity and Reliability Test of the WHOQOL-HIV BREF Instrument on PLHIV in Bandar Lampung City in 2025 - Prahastuti, Brian Sri; Endarti, Ajeng Tias; Solikhin, M Halfani (LPPM Universitas Mohammad Husni Thamrin, 2025)
Quality of life (QoL) is an essential indicator for assessing the physical, psychological, social, and spiritual well-being of People Living with HIV (PLHIV). For people living with HIV (PLHIV), this concept is particularly important because HIV infection is chronic and requires long-term therapy, which carries various clinical and psychosocial consequences. The impact of HIV is not only related to physiological changes but also emotional and social problems caused by societal stigma and discrimination. Measuring the quality of life of people living with HIV requires valid, reliable instruments that accurately reflect the patient's condition. The WHOQOL-HIV BREF is an instrument developed by the World Health Organization to measure QoL among PLHIV across six main domains. This study aimed to evaluate the validity and reliability of the Indonesian version of WHOQOL-HIV BREF among PLHIV in Bandar Lampung City in 2025. A cross-sectional design was employed, using purposive sampling to recruit PLHIV who met the inclusion criteria. The Indonesian version of WHOQOL-HIV BREF was administered as the research instrument. Validity testing was conducted using item-total correlation analysis, while reliability testing employed Cronbach’s Alpha coefficient. The results showed that all 31 items of the WHOQOL-HIV BREF were valid (r‑calculated > r‑table 0.349), indicating that the instrument is suitable for assessing the quality of life of PLHIV. These findings provide a strong basis for the implementation of WHOQOL-HIV BREF in clinical practice, research, and health program planning for PLHIV at the local level..